2013
DOI: 10.1099/jmm.0.052373-0
|View full text |Cite
|
Sign up to set email alerts
|

SubMICs of penicillin and erythromycin enhance biofilm formation and hydrophobicity of Corynebacterium diphtheriae strains

Abstract: Subinhibitory concentrations (subMICs) of antibiotics may alter bacterial surface properties and change microbial physiology. This study aimed to investigate the effect of a subMIC (F MIC) of penicillin (PEN) and erythromycin (ERY) on bacterial morphology, haemagglutinating activity, cellsurface hydrophobicity (CSH) and biofilm formation on glass and polystyrene surfaces, as well as the distribution of cell-surface acidic anionic residues of Corynebacterium diphtheriae strains (HC01 tox " strain; CDC-E8392 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
(55 reference statements)
2
15
1
3
Order By: Relevance
“…Numerous studies have shown that b-lactams below their MIC (e.g. 1/4 and 1/2 MIC) could induce biofilm formation of different bacterial species (Ahmed et al, 2009;Davies et al, 2006;Frank et al, 2007;Gomes et al, 2013;Kaplan, 2011;Mirani and Jamil, 2011;Nucleo et al, 2009;Wu et al, 2014). Our findings demonstrated that 1/2 MIC of penicillin G induced biofilm formation in A. pleuropneumoniae.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Numerous studies have shown that b-lactams below their MIC (e.g. 1/4 and 1/2 MIC) could induce biofilm formation of different bacterial species (Ahmed et al, 2009;Davies et al, 2006;Frank et al, 2007;Gomes et al, 2013;Kaplan, 2011;Mirani and Jamil, 2011;Nucleo et al, 2009;Wu et al, 2014). Our findings demonstrated that 1/2 MIC of penicillin G induced biofilm formation in A. pleuropneumoniae.…”
Section: Discussionmentioning
confidence: 48%
“…On the other hand, exposing P. aeruginosa to sub-MIC of imipenem resulted in the up-regulation of genes involved in alginate biosynthesis (Bagge et al, 2004). Recently, Gomes et al (2013) demonstrated that sub-MIC of penicillin induced bacterial filamentation, cell-surface hydrophobicity of Corynebacterium diphtheriae and increased biofilm formation. Thus, the purpose of this study was to evaluate the effect of sub-MIC of penicillin G on the biofilm formation by field isolates of A. pleuropneumoniae.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Accordingly, Goulter et al 23 also reported a significant correlation between hydrophobicity, attachment and biofilm-formation ability in bacteria. Gomes et al 24 reported that sub-MICs of penicillin and erythromycin enhance cell-surface hydrophobicity and biofilm formation. This particular feature of resistant bacteria has a major role in bacterial survival inside the host.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that biofilm formation upon exposure to subinhibitory concentrations of antibiotics may represent and inducible mechanism of antibiotic resistance (Kaplan, 2011). This antimicrobialinduced biofilm formation would account for the difficulties to eradicate recurrent bacterial infections in clinic diseases (Berditsch et al, 2012;Kaplan et al, 2012;Abdelhady et al, 2013;Gomes et al, 2013).…”
Section: Biofilms As Antibiotic Induced Resistance Mechanismsmentioning
confidence: 99%